NILAI-NILAI SEJARAH DAN FILOSOFI PADA ARSITEKTUR RUMAH PANGGUNG MASYARAKAT GORONTALO - Heryati . (Jurnal Inovasi, 2011)
Architectural House Stage Gorontalo is one physical manifestation of Gorontalo produced by society. But its existence is now extinct due to advances in technology, and public misunderstanding of the values contained in this stage house architecture. This research aims to reveal the characteristics of the original dwelling house Gorontalo society in ancient times and the values contained in it by looking at historical and cultural background of the people of Gorontalo. This research was conducted using a qualitative approach. Ways of collecting data through observation, measurement and interview, and then discussed descriptively. The results show the public the original dwelling house Gorontalo shaped stage in antiquity can be differentiated based on the status / social strata of society, namely the category to house kings/nobles, homes for the rich and home to most of society. This specification can be seen from the scale space/house (space complexity), number of stairs, roof forms and ornamentation. Type form residential communities shaped stage based on Gorontalo most Gorontalo historical background that shaped the kingdom as well as traditional values and Islamic law which is still firmly held by the people of Gorontalo.